Pengendalian Kualitas Produk Lembaran Serat Semen Rata di Pt Bakrie Building Industries Dengan Metode DMAIC - Ho Hwi Chie; Muhammad Zaky Ambadar; Wahyu Hidayat; Sutan Rieza Abdillah (Bina Nusantara University, 2010)
Producing quality products to match customer expectations is an important thing that needs to be done by every company that produces any product, to gain public appreciation and sell their products on the market. Therefore companies need to have a strong commitment in improving and maintaining product quality. The study related to product quality of flat sheets of fiber cement or more commonly known as versaboard produced by PT. Bakrie Building Industries show that there are 9 (nine) types of defects that can degrade the quality of production. Most dominant defects occured on 3 (three) versaboard products, the crack (2.03%), broken end (0.80%) and side trim (0.35%) during observation. Sigma level of products is obtained at 4:16 at a cost saving of due to defects of Rp.14.645.600, 00. Defects that occur tend to be caused by methods, people, machines, and materials used. Efforts to reduce the level of defects are done by making the SOP of the break-up method, and manufacture of cutter flow diagram. REBA score calculation results (Rapid Entire Body Assessment) in the removal and break-up reduction is obtained at 8 with a high level of risk should lead to improving the position of the operator using the Rapid Entire Body Assessment (Reba) so that operators can work more carefully and responsibly..